Population-Based Study of the Association between Urbanization and Kawasaki Disease in Taiwan - Wei-Pin Chang; Shyh-Jong Wu; Wei-Chiao Chang; Ho-Chang Kuo (The Scientific World Journal)
Background. It is unclear if the prevalence of Kawasaki disease (KD) correlates with the degree of urbanization. We hypothesized that the prevalence of KD is more pronounced in urban versus rural environments. Methods. The National Health Insurance (NHI) program was implemented in Taiwan in 1995 and covers most of the population (>99%). We used the NHI database to investigate the epidemiological features of KD. A total of 115 diagnosed patients with KD from 1997 to 2010 were included, together with 1,150 matched controls without KD. Chi-square analyses were performed to investigate the difference between modern city and rural environments. Results. Of the 1265 sampled subjects (claims data from 1,000,000 random subjects), the mean age of the KD study group and control group was 2.08 ± 1.66 and 2.08 ± 1.64 years, respectively. After matching for age, sex, and same index date, no statistically significant differences in urbanization level and geographical location of the patients' residence were observed. Conclusion. Urbanization did not appear to be an important effect modifier of Kawasaki disease in Taiwan.